ILMU USHUL FIQH (Kajian Ontologis dan Aksiologis) - Muhyar Fanani (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2009)
At first, Islamic law is a law which encompasses all aspects oflife. In reality, Islamic law only becomes a marginal law. Most ofobservers said that its fault is on the methodology aspect that isIslamic legal theory. Therefore, the effort of this theorydevelopment cannot be avoided. The figures of Islamic legaltheory such as Fazlur Rahman (Pakistan), MahmoudMuhammad Taha (Sudan), Abdullahi Ahmed an-Na’im (Sudan-USA), Muhammad Sa’id Asymawi (Egypt), and Abd al-HamidA. Sulaymân (Arab-Malay) remind Moslems to develop thistheory. This writing tries to accept their invitation based onphilosophy perspective, that is a perspective which has not beenused by them.